2019
DOI: 10.1017/jfm.2019.486
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of viscoelastic pipe flow at low Reynolds numbers in the maximum drag reduction limit

Abstract: Polymer additives can substantially reduce the drag of turbulent flows and the upper limit, the so-called state of ‘maximum drag reduction’ (MDR), is to a good approximation independent of the type of polymer and solvent used. Until recently, the consensus was that, in this limit, flows are in a marginal state where only a minimal level of turbulence activity persists. Observations in direct numerical simulations at low Reynolds numbers ( $Re$ ) using minimal sized channels appeared t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
104
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(123 citation statements)
references
References 33 publications
19
104
0
Order By: Relevance
“…Importantly, the instability continues to exist for the experimentally relevant values of Dλ/R 2 ∼ 10 −9 -10 −7 , but would be suppressed at much larger values of Dλ/R 2 ∼ 10 −4 -10 −2 (or, equivalently, Sc < 1000, for E ∼ 0.1) used in earlier DNS studies FIGURE 27. The effect of stress diffusion (characterized by Dλ/R 2 ) on the threshold Re required for onset of instability at different E, β and k. (Sureshkumar & Beris 1995;Sureshkumar et al 1997;Lopez et al 2019). Thus, consistent with the results of Sid et al (2018), the results of figure 27 reinforce the importance of using simulation techniques, which avoid an artificially enhanced diffusivity, to access the axisymmetric structures associated with the centre-mode instability.…”
Section: Role Of Stress Diffusion On the Unstable Centre Modesupporting
confidence: 76%
See 3 more Smart Citations
“…Importantly, the instability continues to exist for the experimentally relevant values of Dλ/R 2 ∼ 10 −9 -10 −7 , but would be suppressed at much larger values of Dλ/R 2 ∼ 10 −4 -10 −2 (or, equivalently, Sc < 1000, for E ∼ 0.1) used in earlier DNS studies FIGURE 27. The effect of stress diffusion (characterized by Dλ/R 2 ) on the threshold Re required for onset of instability at different E, β and k. (Sureshkumar & Beris 1995;Sureshkumar et al 1997;Lopez et al 2019). Thus, consistent with the results of Sid et al (2018), the results of figure 27 reinforce the importance of using simulation techniques, which avoid an artificially enhanced diffusivity, to access the axisymmetric structures associated with the centre-mode instability.…”
Section: Role Of Stress Diffusion On the Unstable Centre Modesupporting
confidence: 76%
“…It is worth emphasizing that all of the experiments on viscoelastic transition (with the exception of Srinivas & Kumaran 2017) pertain to the pipe geometry. Further, and importantly, recent simulations in both the channel (Samanta et al 2013;Sid et al 2018) and pipe (Lopez et al 2019) geometries have found analogous (span-wise oriented) coherent structures, suggesting a common underlying mechanism for elasto-inertial transition.…”
Section: Centre Versus Wall Modes In Viscoelastic Pipe and Channel Flowsmentioning
confidence: 75%
See 2 more Smart Citations
“…Moreover, recent studies have shed light on the origin of the maximum drag reduction (MDR), namely, in this regime the flow dynamics is driven by an elasto-inertial instability (Dubief, Terrapon & Soria 2013;Samanta et al 2013;Li, Sureshkumar & Khomami 2015;Sid, Terrapon & Dubief 2018) that could even eliminate Newtonian turbulence (NT). Furthermore, flow relaminarization has recently been observed in channel and pipe flows of polymeric solutions as polymer concentration (elasticity level) is increased at the transition Re (Choueiri, Lopez & Hof 2018;Lopez, Choueiri & Hof 2019;Shekar et al 2019;Chandra, Shankar & Das 2020). Specifically, the MDR state is achieved via a reverse transition pathway from NT through a relaminarized state.…”
Section: Introductionmentioning
confidence: 99%